Pengaruh Penerapan Model Pembelajaran Logan Avenue Problem Solving (LAPS-Heuristik) terhadap Kemampuan Pemecahan Masalah pada Soal Cerita Barisan dan Deret Aritmetika - Nindya Tifa Novitasari; Ali Shodikin (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
The poor problem solving abilities of students is still a scourge in mathematics learning, mainly in terms of solving mathematical story problems. This is because in the case of story problems, students are required to understand the information and the questions in mathematical problems at the beginning in order to create a mathematical model which reflects the problem being solved. This study aimed to examine the achievement and improvement of students’ abilities in solving mathematical story problems about arithmetic sequences and series using LAPS-Heuristic learning model. The study method was the Intact-Group Comparison. The subjects were 43 students who were divided into two groups. The first group received conventional learning, while the other group received LAPS-Heuristic learning. The results showed that both achievement and improvement of students’ abilities in solving mathematical story problems who received LAPS-Heuristic learning model were better than in students’ abilities who received conventional learning.